Exergy Assessment of the Hydrocracking Process with Mass and Energy Optimization: an Industrial-scale Study - Luisa Acosta-Esalas; Sofia Garcia-Maza; Angel D. Gonzalez-Delgado (Chemical Engineering Transactions)
Hydrocracking is a key process in petroleum refining, where catalytic cracking is combined with hydrogenation to transform heavy feedstocks into lighter and commercially valuable products. This work focuses on improving the energy efficiency of a hydrocracking unit, also incorporating the reuse of wastewater streams generated within the process itself. Using the Aspen Hysys V.14 simulation tool, a detailed energy analysis was performed to identify the main sources of energy loss in the process. The results show that the overall efficiency of the process is high (98.08%), but the Hydrogen Purification stage presents the highest exergy destruction (915,717.71 MJ/h), due to the residues generated from the separation processes in the absorption and adsorption towers, where contaminants such as NH3 and H2S are removed from the hydrogen streams. The analysis reveals the need to improve the efficiency of this stage to increase the sustainability of the overall process. By identifying the areas of greatest energy loss, this study provides a solid basis for proposing improvements and optimizing the operation of the hydrocracking plant.